İsmail B. Uleyye ve hadis ilmindeki yeri - Sabuncu, Mahmut (My University, 2018)
İsmâil b. Uleyye (ö. 193/ 809), tebe-i tâbiîn âlimlerinden olup ilmî mesâisini Basra’da sürdürmüş, mezâlim (en yüksek idarî-yargı denetleme kurumu) görevi için gittiği Bağdat’ta hicrî 193 yılında vefat etmiştir. Eyyûb es-Sahtiyânî (ö. 131/ 749) gibi dönemin önemli âlimlerinin tedrisinden geçip ders halkalarında yetişen İbn Uleyye, cerh-tadîl ilminde otorite olan âlimler tarafından güvenilirliğine matuf lafızlarla tevsik edilmiştir. Ebû Bekr b. Ebû Şeybe (ö. 235/ 849) ve Ahmed b. Hanbel (ö. 241/ 855) gibi Ehl-i hadis’in önemli simâlarına hocalık yapmıştır. Bu çalışmada, Basra’da yetişmiş bir âlim olan İsmâil b. Uleyye’nin hayatı ve hadisçiliği ele alınmıştır. Söz konusu kısımlar incelenirken İbn Uleyye’nin yetiştiği ilmî, sosyal ve siyâsi ortama da değinilmiştir. Bunun yanında İbn Uleyye’nin Kütüb-i Sitte’deki rivayetleri hocaları, talebeleri ve konuları bakımından ele alınmıştır. Hangi hocalarından daha fazla rivayet ettiği, rivayetlerinin hangi konularda olduğu ve rivayetinin çok olduğu hocalarının meclislerinin mahiyeti araştırılmıştır. Bu araştırmanın neticesinde İbn Uleyye’nin Ehl-i hadis’in fukaha çizgisinde bir âlim olduğu anlaşılmıştır.

Ismail bin Ulayya (d. 193/ 809) is one of the scholars among the successors of the successors. He carried out his scientific studies in Basra. Later on, he went to Baghdad to fulfill the duty of Mazālim, the supreme supervisory council of administration and justice, and he died in 193 (H) in Baghdad. He took many courses from the important scholars of the era like Ayyoub Al-Sahtiyānī (d. 131/ 749) and he grew in such scientific circles. He was certified by authority figures in jarh and ta’dil (verification and falsification) field through some wordings referring to his authenticity. Some significant personalities of Ahl Al-Hadith (people of the tradition) as Abou Bakr bin Abou Shayba (d. 235/ 849) and Ahmad bin Hanbal (d. 241/ 855) were disciple of Ibn Uyayna.In this study, we have examined the life of Ismail bin Ulayya, who was a scholarly person grown up in Basra, and his speciality on the science of Hadith. While we were analysing these topics, also we dealt with scientific, social and political environment in which Ibn Ulayya grew up. Moreover, his reports in the Six Books were handled in terms of his masters, disciples and topics. Additionally, we took into consideration that from which masters he transmitted mostly, in which topics his reports and the quality of majlises of the masters he reported more. As a result of this research, we have achieved that Ibn Ulayya is a scholar on the line of the legal branch of Ahl Al-Hadith.
Keywords: Basra; Hadis; Hadith; hicrî ikinci asır; İsmâil b. Ulayya; İsmâil b. Uleyye; tebe-i tâbiîn; the second hijri age